GAMBARAN STROKE PADA WANITA DI RSUPN CIPTO MANGUNKUSUMO - Sheila Agustini*, Arie Khairani*, Freddy Sitorus* (NEURONA, 2010)
AIM TO DESCRIBE THE PREVALENCE OF STROKE IN WOMEN MAJOR RISK FACTORS AND CORRELATION OF RISK FACTORS WITH CERTAIN AGE GROUP